ANALYSIS OF MURABAHAH FINANCING FOR GOLD INSTALLMENT PRODUCT AT BANK SYARIAH INDONESIA BRANCH OFFICE MAGELANG GATOT SUBROTO - Erissa Zumarnis; Chaidir Iswanaji; Nibras Anny Kahbibah (Transpublika Publisher, 2024)
This study aims to investigate the implementation of Murabahah financing, the challenges encountered in implementing Murabahah financing, and the strategies employed to overcome these obstacles at Bank Syariah Indonesia Magelang Gatot Subroto Sub-Branch Office. The research utilizes both secondary and primary data, with data collection techniques including interviews. The study adopts a qualitative research approach. The findings reveal that the Murabahah Agreement is established when a customer wishes to purchase gold from the bank in installments over an agreed period of time. The term